ORAL WAYAK TRADITION OF WEST LAMPUNG PEOPLE - Armina Armina (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2014)
Oral Wayak Tradition, is a kind of poetry of verse used by the West Lampung people in form a monologue or dialogue. Wayak used as an introduction to custom events, complementary events to the release of the bride groom, complement of traditional dance events, complementary events of teens event (miyah damagh), hum the children to sleep and for emjoyment. The research problem related to the functions and values of any moral contained in Oral Wayak, that became popular in the West Lampung from until nowadays. This study aims to describe the functions and moral values contained in Wayak which associated with society's perspective of West Lampung towards Wayak. This study includes the type of qualitative research using ethnographic design to perform textual analysis of the Oral Wayak tradition in reconstructing cultural structure. The data in this study are texts of Oral Wayak tradition, notes on cultural traditions, and rituals of the traditional wedding ceremony, examined through the functions and values contained in the texts of oral Wayak tradition. Data in the form of oral speech is the focus of the primary data analysis. Data collected through the study of documents, interviews and observations. In collecting data, the researcher serves as a key instrument. Wayak function in the West Lampung community, generally as a medium of expression of heart (from man to the girl or vice versa), as a tool entertainer of the atmosphere relaxing or relieving boredom and become tools used cangget events complement traditional dances. On the other hand, the function can be considered to educate and engage listeners on matters relating to the conduct and behavior. In general, people from all walks of West Lampung can enjoy Wayak. Wayak enjoyed by urban and rural residents, the educated class and the laity, as well as by customary and religious groups. This suggests that oral tradition is still maintained by the public Wayak West Lampung from the beginning until now. In West Lampung, oral tradition Wayak have revealed a number of moral values which are the responsibility and obligation to be firmly held together as a value that can be flashed and manifested as a representation of ethical value in building and live together, it is agreed as the norm both outer and inner personality.